Pengembangan Gim Serius Untuk Pengenalan Jamu Menggunakan Metodologi Putaran Permainan - Dimas Putra Andaru; Pratama Wirya Atmaja; Firza Prima Aditiawan (Pusat Riset dan Inovasi Nasional, 2024)
Jamu is a traditional herbal beverage that represents a cultural heritage with various health benefits. Despite this, adolescents tend to turn to chemical medications. This research proposes the development of an educational and engaging serious game to introduce jamu to the adolescent age group. The gameplay loop methodology is employed to ensure optimal connectivity between the game system and jamu educational content. The game design has been successfully implemented in the development of the game using the Unity game engine, resulting in an educational game based on significance testing and GUESS validation. The game is also deemed engaging based on the correlation test results. The Gameplay Loop method successfully maintains the connectivity between educational content and the game system, indicating that the game effectively imparts understanding of jamu to its players.